Influence of teachers’ self-efficacy on secondary school students’ self-efficacy in biology in Ogbomoso, Nigeria - Mulkah Adebisi Ahmed; Ahmed Abiodun Lawal; Rihanat Aduke Ahmed (JPBI (Jurnal Pendidikan Biologi Indonesia), 2022)
It is widely proven by several studies that efficacy is an important factor in the teaching-learning process. Therefore, the goal of this study was to examine whether teachers’ self-efficacy contributes to the development of students’ self-efficacy in Biology. This study was a descriptive research with survey type which used proportionate and stratified sampling techniques to select 98 secondary schools in Ogbomoso, Nigeria. Proportionate, purposive, and simple random sampling techniques were used to select 207 biology teachers and 392 SSS I and II biology students based on gender. The data collected were analysed using mean scores, chi-square, and regression analysis at 0.05 level of significance. The findings revealed that: 1) there was a positive correlation between teachers’ self-efficacy and students’ self-efficacy in biology; 2) the level of teachers’ self-efficacy was moderately high; and 3) female students have higher self-efficacy than male students in biology. The study concluded that teachers’ self-efficacy influences their students’ self-efficacy. Thus, it is recommended that biology teachers should be responsible and pay more attention to the development of their students’ self-efficacy irrespective of students’ gender.